2015
DOI: 10.1099/jgv.0.000025
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric neuraminidase and mutant PB1 gene constellation improves growth and yield of H5N1 vaccine candidate virus

Abstract: We previously showed that a mutated PB1 gene improved the growth kinetics of a H3N2 influenza reassortant. Here, we showed that the same mutations improved the growth kinetics of a virus containing the A/Vietnam/1203/2004 (H5N1) haemagglutinin and neuraminidase (NA). Total protein yield and NA activity were increased when a chimeric NA was included. These increases indicated that the synergistic effect was due to the gene constellation containing both the altered PB1 gene and the chimeric NA gene.The object of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several studies have used reverse genetics to change the virion incorporation of HA or NA by altering the promoter region, codons, or Nlinked glycosylation sites in their respective gene segment [7,[19][20][21]. Similar investigations have found that exchanging the internal gene segments can also affect the NA and HA amounts in virions [22][23][24][25], a trait supported by more mechanistic analysis of NA and HA expression in cells [26,27]. Here, we investigated if the PR8 influenza vaccine virus backbone can be modified to increase the NA virion content and balance the HA and NA antibody responses while preserving both antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used reverse genetics to change the virion incorporation of HA or NA by altering the promoter region, codons, or Nlinked glycosylation sites in their respective gene segment [7,[19][20][21]. Similar investigations have found that exchanging the internal gene segments can also affect the NA and HA amounts in virions [22][23][24][25], a trait supported by more mechanistic analysis of NA and HA expression in cells [26,27]. Here, we investigated if the PR8 influenza vaccine virus backbone can be modified to increase the NA virion content and balance the HA and NA antibody responses while preserving both antigens.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several approaches have been employed to improve antigen yield of candidate vaccine viruses made by reverse genetics. These have involved empirical testing and selection of PR8 variants (11, 12), as well as targeted approaches such as making chimeric genes containing promoter and packaging signal regions of PR8 while encoding the ectodomain of the CVV glycoprotein genes (1321) or introducing a wild-type (WT) virus-derived segment 2 (2129). Our approach was to manipulate expression of an accessory protein virulence factor, PA-X (30).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several approaches have been employed to improve antigen yield of candidate vaccine viruses made by reverse genetics. These have involved empirical testing and selection of PR8 variants (11, 12), as well as targeted approaches such as making chimeric genes containing promoter and packaging signal regions of PR8 while encoding the ectodomain of the CVV glycoprotein genes (13-21), or introducing a wild-type (WT) virus-derived segment 2 (21-29). Our approach was to manipulate expression of an accessory protein virulence factor, PA-X (30).…”
Section: Introductionmentioning
confidence: 99%